Conductive long fibre reinforced thermoplastics by using carbon nanofibres - Hattum, F. W. J. van (2006)
In the present work conductive semistructural composites were produced by injection moulding, combining the mechanical properties of long (glass) fibre thermoplastics (LFTs) with the conductive properties of carbon nanofibres (CNFs). The moulded LFT/CNF parts exhibit percolation behaviour between 2 and 3 wt-%CNF loading, characterised by a sharp drop in electrical resistivity from 1012 to 102 V cm, accompanied by a step increase in the shear viscosity at low shear rates. At the same time, the main LFT properties are maintained: the modulus increased slightly, strength and viscosity, and thus processability, remained unaffected, while the impact resistance decreased. In addition, a significant improvement in surface quality was observed, largely eliminating the glass fibre printthrough, typically found in LFTs. The results thus show the successful use of small amounts of CNFs in making LFTs conductive, which becomes suitable for, e.g. electrostatic painting at limited additional cost